Development of College Libraries in Mizoram: Challenges and Prospects for College Libraries in Mizoram (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The paper discusses role of library in higher education and its establishment of College libraries in Mizoram. It highlights problems and some features of the College libraries with its services and also suggests for its future development in Mizoram.